2012
DOI: 10.3184/095422912x13257005726800
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in water and sediment samples from Ismaelia Canal using ion chromatography and atomic absorption spectroscopy

Abstract: Two analytical techniques, atomic absorption spectroscopy and ion chromatography, have been used to analyse the heavy element content in water and sediments from the Ismaelia Canal, Egypt. The water samples were collected from a depth of 1.5 m below the surface while the pH of the samples was adjusted by nitric acid to prevent the adsorption of the elements onto the walls of the sample container. The elements studied were copper, lead, iron, nickel, cobalt, cadmium and manganese. For the analysis using ion chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Organic carbon was determined, following Reference [28]. Fe, Cu, Zn, and Mn were determined by atomic absorption spectrophotometry (AASVario 6, Jena, Germany) [29]. Nitrogen was determined using the Kjeldahl method [30] and phosphorus was determined via the phosphomolybdic acid method [31].…”
Section: Plant Material Soil Mixes Ala Treatment and Inoculum Prepmentioning
confidence: 99%
“…Organic carbon was determined, following Reference [28]. Fe, Cu, Zn, and Mn were determined by atomic absorption spectrophotometry (AASVario 6, Jena, Germany) [29]. Nitrogen was determined using the Kjeldahl method [30] and phosphorus was determined via the phosphomolybdic acid method [31].…”
Section: Plant Material Soil Mixes Ala Treatment and Inoculum Prepmentioning
confidence: 99%
“…Sediment samples were also collected into clean zip-lock bags at each sampling locations using the Eckman grab. The collected samples were transported to the laboratory under mild aeration for the determination of copper Mohamed et al (2012), while the sulphate levels were determined using titrimetric method as reported in Fritz and Freeland (1954).…”
Section: Sediment and Water Samples Collection And Fungicide Analysismentioning
confidence: 99%
“…Atomic absorption spectroscopy (AAS) is a frequently used instrumental technique for the determination of trace heavy metal ions because of its low cost and short analysis time. 10 Waters of Kosovo have been poorly investigated. Gashi et al 11 performed the first step with the investigation of the rivers Drini i Bardhë, Morava e Binçës, Lepenc and Sitnica, which was of supra-regional interest.…”
Section: Introductionmentioning
confidence: 99%